Design and Implementation of Boost Voltage Doubler for Maximum Power Point Tracker Application Using STM32F1038CT - Laras Triefena; Leonardus H. Pratomo; Slamet Riyadi; F. Budi Setiawan (JURNAL INFOTEL, 2020)
Photovoltaic is an absolute device in the solar power plant system. A DC-DC converter with a maximum power point tracker (MPPT) algorithm is required to obtain the maximum power of photovoltaic. In general, solar power plant applications used a two-stage converter: the first stage is boosting DC-DC converter, and the second stage is the multilevel Inverter. Boost DC-DC converter is usually implemented singly, which causes many boost DC-DC converters to be implemented in a solar power plant application. The voltage doubler type boost DC-DC converter proposed in this paper is to simplify the circuit so that there is only one converter in a solar power plant application. This converter principle combines two conventional boost converters, which are integrated into one so that the power circuit and control circuit form become simpler. This proposal is verified through computation simulation and hardware design using the STM32F1038CT microcontroller for the final verification. The efficiency algorithm of the simulation is 99.7%, and the hardware experimental is 85.65%